Association of Sleep Disordered Breathing with Mono-Symptomatic Nocturnal Enuresis: A Study among School Children of Central India. - Bharat Choudhary; Rajesh Patil; Girish Chandra Bhatt; Abhijit P Pakhare; Abhishek Goyal; Aswin P; Bhavna Dhingra; K C Tamaria (PLoS ONE, 2016)
Objective To study the prevalence of primary monosymptopomatic nocturnal enuresis (PMNE) in children aged 5-10 year and to find its association with sleep disordered breathing (SDB) by using a 22 item pediatric sleep related breathing disorder (SRBD) scale. Methods This was a school based cross sectional epidemiological study from July 2015 to November 2015. A questionnaire seeking information on socio-demographic variables, nocturnal enuresis (NE) frequency, school performance and a validated 22 item pediatric sleep related breathing disorder scale (SRBDs) was distributed to 1820 pupils in three primary schools. Results A total of 1528(83.95%) questionnaires were retrieved. Out of 1528 forms, 182(11.9%) forms were incomplete for requested information and hence 1346 (73.9%) questionnaires were finally analyzed. The prevalence of NE was found to be 12.7% (95% CI; 11-14.6), whereas prevalence of primary nocturnal enuresis (PMNE) was 8.2% (95% CI; 7.1-10.1). SRBD scale score >0.33 (adjusted OR: 2.87; 95%CI: 1.67-4.92), paternal history of enuresis in childhood (adjusted OR:4.96; 95% CI: 2.36-10.45), and inappropriate toilet training (adjusted OR: 1.64; 95% CI: 1.01-2.66) were independently associated with PMNE. Conclusion Sleep disordered breathing, inappropriate toilet training and a history of childhood NE in father were found to be significant risk factors for PMNE in the present study. Thus, these findings suggest that it is imperative to rule out SDB in PMNE patients as they may require different therapeutic interventions.